2010
DOI: 10.3109/10611861003733995
|View full text |Cite
|
Sign up to set email alerts
|

SDS-coated atovaquone nanosuspensions show improved therapeutic efficacy against experimental acquired and reactivated toxoplasmosis by improving passage of gastrointestinal and blood–brain barriers

Abstract: Toxoplasmic encephalitis (TE) is the most common clinical manifestation of reactivated infection with Toxoplasma gondii in immunocompromised patients that is lethal if untreated. The combination of pyrimethamine plus sulfadiazine or clindamycin is the standard therapy for the treatment of TE, but these combinations are associated with hematologic toxicity and/or life-threatening allergic reactions. Therefore, alternative treatment options are needed. Atovaquone is safe and highly effective against T. gondii in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 33 publications
0
29
0
4
Order By: Relevance
“…İmmün yetmezlikli hastalarda reaktivasyonun en yaygın klinik göstergelerinden olan toksoplazmik ensefalit (TE), tedavi edilmediğinde öldürücü olmaktadır 6 . Avrupa'da yapılan bir çalışmada, AIDS ve toksoplazmoz pozitif olan hastaların %47'sinde TE görülmüştür 12 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…İmmün yetmezlikli hastalarda reaktivasyonun en yaygın klinik göstergelerinden olan toksoplazmik ensefalit (TE), tedavi edilmediğinde öldürücü olmaktadır 6 . Avrupa'da yapılan bir çalışmada, AIDS ve toksoplazmoz pozitif olan hastaların %47'sinde TE görülmüştür 12 .…”
Section: Discussionunclassified
“…yonlar ya da hematolojik toksisitenin ortaya çıktığı gözlenmektedir 6,10 . AIDS hastalarında ve klasik toksoplazmoz tedavisine yanıt vermeyen hastalarda 750 mg atovakuon, günde 4 kez tablet formunda kullanılmış ve 6 hafta sonunda radyolojik görüntüler ile klinik tabloda iyileşmeler gözlemlenmiştir 19 .…”
Section: Mi̇krobi̇yoloji̇ Bülteni̇unclassified
See 2 more Smart Citations
“…Nanosuspensions exhibited improved serum levels and higher levels in brain tissues resulting in an improved oral bioavailability [34]. Polysorbate 80 and sodium cholate-coated amphotericin B nanosuspensions showed improved delivery to the brain and amebicidal activity against Balamuthia mandrillaris [35]. Also nimodipine nanosuspension (300 and 650 nm) in separate studies produced by HPH coated with Tween 80 showed significant higher concentration in MPS-rich organs [36].…”
Section: Surface Modification Of Nanonized Crystalsmentioning
confidence: 99%